PELAKSANAAN PEMBELAJARAN BIOLOGI KURIKULUM BERBASIS CINTA PADA SEKOLAH MADRASAH IBTIDAIYAH - Sandi Akib; Ardila Ardila; Ahmad Zainuri; Frika Farimah Zahra (CV. ADIBA AISHA AMIRA (ADISAM PUBLISHER), 2025)
This paper discusses the implementation of biology learning in Madrasah Ibtidaiyah (MI) using the Love-Based Curriculum (KBC). The objectives of this study are (1) to describe the principles of KBC and its adaptation to basic biology material, (2) to identify teaching methods that are in line with the values of love (empathy, appreciation of creation, environmental responsibility), and (3) to present a case study of implementation based on document and literature analysis. The results of the study show that KBC can strengthen students' motivation, character, and science literacy if integrated through thematic learning, local-based projects, and authentic assessment; the main obstacles include teacher readiness, availability of adaptive teaching materials, and policy training support. Recommended practices include the development of local modules, teacher training in humanistic pedagogy, and continuous evaluation.